Progression of vertebral fractures in metastatic melanoma and non-small cell lung cancer patients given immune checkpoint inhibitors - Marco Meazza Prina; Andrea Alberti; Valeria Tovazzi; Marco Ravanelli; Greta Schivardi; Alice Baggi; Luca Ammoni; Lucilla Guarneri; Francesca Salvotti; Manuel Zamparini; Davide Farina; Margherita Parolise; et al. (Journal of Bone Oncology)
Introduction: The immune system mediates important effects on bone metabolism, but little has been done to understand immunotherapy’s role in this interaction. This study aims to describe and identify risk factors for the occurrence and/or exacerbation of vertebral fractures (vertebral fracture progression) during immune checkpoint inhibitors (ICIs). Methods: We conducted an observational, retrospective, monocentric study. We collected data on melanoma and NSCLC patients, treated with first-line ICIs at the Medical Oncology Department ASST Spedali Civili of Brescia, between January 2015 and November 2021, and with a median follow-up of 20.1 (6–36) months. We collected data on patients, diseases, immune-related adverse events, and cortico-steroid therapy initiated on concomitant ICIs. Results: We identified 135 patients, 65 (48.2 %) with locally advanced/metastatic melanoma and 70 (51.8 %) with locally advanced/metastatic non-small cell lung cancer (NSCLC). Twenty-one (15.6 %) patients already had an asymptomatic vertebral fracture at baseline before starting ICIs in monotherapy. A total of ten patients, or 7.4 %, had a vertebra fracture progression defined as a new vertebral fracture or a worsening of a previous fracture. There was a strong relation between the steroid therapy and irAEs with vertebra fracture progression [OR (95 % CI) 8.1 (3.7–17.8) p-value < 0.001] in univariable analysis. However, only steroid therapy resulted to be an independent risk factor [8.260 (95 % CI 0.909–75.095); p-value 0.061] at the multivariable analysis. Conclusion: Concurrent steroid therapy in patients receiving immunotherapy exposes them to a high risk of fractures due to skeletal fragility. The use of bone resorption inhibitors should be considered in these patients to prevent these adverse events.